2021
DOI: 10.3390/bs11120181
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of the COVID-19 Pandemic on Pregnant Women: A Scoping Review

Abstract: During the gestation period, pregnant women experience physical and psychological changes, which represent vulnerability factors that can boost the development of mental health conditions. The COVID-19 pandemic is producing new changes in the routines of the whole society, especially on lifestyle habits. The psychological impact associated with the COVID-19 pandemic and pregnant women remains unclear. A scoping review regarding the psychological impact of the COVID-19 pandemic on pregnant women was conducted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 69 publications
0
23
0
2
Order By: Relevance
“…Other studies also show that during the pandemic, women report high levels of stress associated with both pregnancy and the COVID-19 pandemic [ 63 ]. According to a review by Campos-Garzón et al [ 64 ] the level of stress experienced by pregnant women is influenced by feelings of loneliness and fear of infection. Moreover, stress has been recognized as a predictor of anxiety and depression symptoms related to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also show that during the pandemic, women report high levels of stress associated with both pregnancy and the COVID-19 pandemic [ 63 ]. According to a review by Campos-Garzón et al [ 64 ] the level of stress experienced by pregnant women is influenced by feelings of loneliness and fear of infection. Moreover, stress has been recognized as a predictor of anxiety and depression symptoms related to COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The null finding with regard to health-related concerns is in contrast with earlier cross-sectional reports that fear of COVID-19 infection was associated with pregnancy-related anxiety and stress [ 5 , 43 ]. A systematic review of 31 studies on anxiety and depressive symptoms in pregnant women showed that fear of contagion and concerns regarding the health of the fetus were major predictors of mental health in these women [ 44 ]. But several of these earlier studies did not simultaneously examine other sources of stress, such as financial difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…This is important, because COVID-19 had a specific psychological impact on women expecting pregnancy, pregnant women, and women with delayed IVF treatment due to the pandemic (e.g. Campos-Garzón et al 2021;Mitrović et al 2021).…”
Section: Methodsmentioning
confidence: 99%